Cultural Aspects in Learning Arabic; Analysis of Learning Media "Aljazeera Learning Arabic" - Mahmudah, Umi; Yahya, Yuangga Kurnia; Fata, Khoirul; Rahmawati, Fitra Awalia (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This study aims to capture the extent to which cultural elements play a role in the media "Aljazeera Learning Arabic" and the portion of its use at beginner, intermediate, and advanced levels. This study is qualitative descriptive research aimed at analyzing the educational media "Aljazeera Learning Arabic" from a cultural perspective. The research object is the media "Aljazeera.Learning.Arabic," with data collected through participatory observation and written documents from the website. The analysis techniques employed include data collection, data reduction, data presentation, and conclusion drawing. The findings reveal that this media consists of three main levels: “al-mubtadi'” (beginner), “al-mutawassith” (intermediate), and “al-mutaqaddim” (advanced). Each level includes several learning themes, which incorporate cultural elements to help students improve their language skills. These cultural aspects are proportionally varied across the levels. At the “al-mubtadi'” level, cultural themes constitute only 36%, while at the “al-mutawassith'” level, they account for 47%. At the “al-mutaqaddim” level, cultural themes dominate, comprising 55% of the total themes. This indicates that cultural content becomes more prominent as the learning level progresses.